Pemetaan Pola Persebaran Gedung Kantor Cabang Dan ATM Bank BCA Di Kota Surabaya Berbasis Pada Sistem Informasi Geografis (SIG) - mirda mirda dwi (Jurnal Vokasi Teknik Sipil, 2024)
Surabaya is the capital of East Java province which is also one of the big cities in Indonesia whose population density is increasing every year. Has an area of 374.36 km2 with a population of 3 million people, making Surabaya a densely populated city. The city of Surabaya is also a trading city in which there is a lot of money circulation. This is evidenced by the many sub-branch offices (KCP) of banks, especially Bank BCA, which are spread across the city of Surabaya. Information regarding the location of Bank BCA Sub-Branch Offices (KCP) is needed so that the people of Surabaya are not too far away from reaching the services offered by KCP Bank BCA. This study aims to determine the mapping, pattern of distribution, and coverage of KCP Bank BCA. This research was conducted using the Nearest Neighbor Analysis method using ArcGIS 10.8 software. The results of the analysis of the distribution pattern of BCA Bank KCP in the Surabaya City area are categorized as random. Outreach results with a radius of 2.5 Km Whereas high coverage results for some areas with a percentage of 35% are in 11 locations, Enough coverage results with a 32% percentage are 10 locations, Low coverage results with a 20% percentage are 6 locations and coverage results are not reached by some areas with a percentage of 13% there are 4 locations.